2006
DOI: 10.1074/jbc.m507393200
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-7 Is Directly Activated by the ∼700-kDa Apoptosome Complex and Is Released as a Stable XIAP-Caspase-7 ∼200-kDa Complex

Abstract: MCF-7 cells lack caspase-3 but undergo mitochondrial-dependent apoptosis via caspase-7 activation. It is assumed that the Apaf-1-caspase-9 apoptosome processes caspase-7 in an analogous manner to that described for caspase-3. However, this has not been validated experimentally, and we have now characterized the caspase-7 activating apoptosome complex in MCF-7 cell lysates activated with dATP/cytochrome c. Apaf-1 oligomerizes to produce ϳ1.4-MDa and ϳ700-kDa apoptosome complexes, and the latter complex directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 52 publications
5
35
0
Order By: Relevance
“…Taken together, the findings of Denault et al [11] agree with other studies, for example with caspase-3-null MCF-7 cell lysates and recombinant apoptosome complexes, which show that only caspase-3 and not caspase-7 produces the p37 form of caspase-9 [1]. However, the study by Denault et al [11] clearly consolidates the view that the most active form of apoptosome-bound caspase-9 contains either the p35 or p37 subunit in conjunction with the p10 subunit.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Taken together, the findings of Denault et al [11] agree with other studies, for example with caspase-3-null MCF-7 cell lysates and recombinant apoptosome complexes, which show that only caspase-3 and not caspase-7 produces the p37 form of caspase-9 [1]. However, the study by Denault et al [11] clearly consolidates the view that the most active form of apoptosome-bound caspase-9 contains either the p35 or p37 subunit in conjunction with the p10 subunit.…”
supporting
confidence: 86%
“…Apaf-1 oligomerizes to form the seven-spoked, wheel-like Apaf-1 apoptosome complex, which recruits caspase-9 to form the active holoenzyme caspase-activating apoptosome complex. This complex then efficiently recruits and directly cleaves procaspase-3 or -7 with high efficiency [1]. However, caspase-9 [like caspase-8 in the DISC (death-inducing signalling complex)] is an unusual caspase in that, in addition to its CARD (caspase-recruiting domain), it has a long interlinker peptide separating the small and large subunit domains.…”
mentioning
confidence: 99%
“…Our results demonstrate that miR-9 overexpression decreases cell viability and increases apoptosis in MCF-7 breast cancer cells. As a caspase-3 null cell line (51), previous studies have shown that DEVDase activity can be increased in MCF-7 cells independent of caspase-3 whereby caspase-7 cleaves DEVD substituting caspase-3 (35,(52)(53)(54). In this study caspase-7 activity was increased, indicating pro-apoptotic activity of miR-9 in MCF-7 cells.…”
Section: Discussionsupporting
confidence: 53%
“…It directly binds to caspases-3, -7, and -9, rendering them inactive (7,34,35). IAPs are characterized by the presence of one or more baculovirus IAP repeat domains and a caspase activation recruitment domain.…”
Section: Discussionmentioning
confidence: 99%